ВПЛИВ ХІМІЧНОЇ ОБРОБКИ ПОВЕРХНІ ЗЕРЕН АЛМАЗУ НА ОТРИМАННЯ ШЛІФПОРОШКІВ АЛМАЗУ З ПІДВИЩЕНОЮ ОДНОРІДНІСТЮ ЗА МІЦНІСТЮ - Ільницька, Галина; Лавріненко, Валерій; Логінова, Ольга; Лисаковський, Валентин; Соколов, Олександр; Смоквина, Володимир; Зайцева, Ірина; Закора, Анатолій; Тимошенко, Вікторія; Котинська, Людмила; Косенчук, Тамара (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2023)
The effect of chemical surface treatment of diamonds synthesized in the Ni-Mn-C system on their strength characteristics is considered. The study was carried out on diamonds of grade AC6, grain size 125/100. Powders before separation according to surface defects were subjected to chemical treatment in a 15 ± 1 % alkali solution with the addition of no more than 3 % hydrogen peroxide for no more than 20 minutes at a boiling temperature. The application of finely dispersed ferromagnetic chalk grains with a chasm size of less than 1000 nm and a concentration of 2.5 ± 0.1% were carried out in a liquid medium with constant stirring for 25±2 min. After application, the water with particles of iron powder that were not fixed was drained, and the diamond powder with iron particles that were fixed on the surface of the grains was dried, and then separated into carried out in a magnetic field on an electromagnetic separator of 138 T at a voltage of 5 to 20 A/m with obtaining four fractions of separation of diamond powders with different surface defects and strength. The conducted studies showed that chemical treatment at the boiling temperature of the solution ensures the cleaning of the surface of diamonds from impurities, as well as from the remains of reagents after the extraction of diamonds from their synthesis product in the form of oxygen-containing functional groups on the surface that interfere with the fixation of metal particles. This ensures the creation of a more developed surface of the diamond grains and contributes to the increase in the selectivity of fixing ferromagnetic particles on the defective areas of the diamond surface. It has been established that the additional chemical processing of diamonds creates a more developed surface of the grains of diamond, which ensures the safety of the extraction of 4 fractions of powders, which are mixed with each other for the coefficient of surface activity Ka from 0.65 to 1.20 % and strength from 11.0 to 4.8 N, differ among themselves by approximately 2.3 times. When diamond grains are cut without chemical processing, powders are removed Ka from 0.58 to 1.10 % and for strength from 8.7 to 5.9 N, which are mixed with each other in about 1.5 times. The uniformity in strength of diamond grinding powders obtained after distribution in a magnetic field with preliminary chemical treatment was about 43 %, while the uniformity in strength of diamond grinding powders without preliminary chemical treatment was about 37 %.